Importance-satisfaction model for quality improvement: the case of higher education - Silva, Fátima H. (2012)
Students are the reason of being of Higher Education Institutions. Times have changed, so their future depends on their capacity to attract and retain students. In this context, it is crucial determining the importance that students place on the product or service attributes that drive their satisfaction with service providers is an essential part of a Higher Education Institutions resource allocation process. An uncomfortable issue is whether importance measures should come directly from students or be derived statistically and, if so, how. This study attempts to determine the key quality factors influencing student’s satisfaction in Higher School of Technology and Management of Bragança (ESTiG), Bragança Polytechnic Institute (IPB) through knowledge of the importance and satisfaction level assigned to each of the factors identified by students. Applying a factor analysis, this study identifies nine quality factors. The research method has an advantage in that it not only identifies the quality factors, but also measures the service quality items of the ESTiG. So, the survey results of this case study demonstrate in general students are satisfied with the service that offers them ESTiG, under to the Importance-Satisfaction Model.